A thermodynamic evaluation on high pressure condenser of double effect absorption refrigeration system. (15th October 2016) - Yılmaz, İbrahim Halil and Saka, Kenan and Kaynakli, Omer
Abstract: One of the parameters affecting the COP of the absorption system can be considered as the thermal balance between the high pressure condenser (HPC) and the low pressure generator (LPG) since heat rejected from the HPC is utilized as an energy source by the LPG. Condensation of the water vapor in the HPC depends on the heat removal via the LPG. This circumstance is significant for making an appropriate design and a controllable system with high performance in practical applications. For this reason, a thermodynamic analysis for the HPC of a double effect series flow water/lithium bromide absorption refrigeration system was emphasized in this study. A simulation was developed to investigate the energy transfer between the HPC and LPG. The results show that the proper designation of the HPC temperature improves the COP and ECOP due its significant impact, and its value necessarily has to be higher than the outlet temperature of the LPG based on the operating scheme. Furthermore, the COP and ECOP of the absorption system can be raised in the range of 9.72–35.09% in case of 2 °C-temperature increment in the HPC under the described conditions to be applied. Highlights: Thermal balance in HPC/LPG unit of a double effect absorption system was studied. A simulation program was developed and its outputs were validated. A parametric study was conducted for a wide range of component temperatures. Proper designation of the HPC temperature improves the COP and ECOP. The system performance raised 9.72–35.09% by controlling the HPC temperature.